2021
DOI: 10.9734/jpri/2021/v33i50b33430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Efficacy of Fenugreek Seed Extract Rinse and Nigella Sativa Seed Extract Rinse against Streptococcus Mutant Colonies

Abstract: Background: Dental infections were caused by the bacterium overgrowth on the surface of the tooth, and treatment should always be set up to prevent this development.Antibiotics have long been used as a conventional antibacterial medication, but their overuse has resulted in microbes gaining resistance to many of the antibiotics, trying to make many commercialized therapeutic remedies ineffectual and resulting to infection recurrence. In this regard we aim to analyze the antibacterial activity of nigella sativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Thymoquinone, an active principle of N. sativa, has been found to possess strong antibacterial properties against Gram-positive bacteria such as S. aureus and Streptococcus mutants. 36 Thymoquinone has been shown to have potency in preventing bacterial biofilm formation. 37 Topical gel formulations prepared using ethylacetate extract of N. sativa have demonstrated antibacterial properties against acne-causing microorganisms, indicating its potential as an alternative remedy for dermal acne.…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone, an active principle of N. sativa, has been found to possess strong antibacterial properties against Gram-positive bacteria such as S. aureus and Streptococcus mutants. 36 Thymoquinone has been shown to have potency in preventing bacterial biofilm formation. 37 Topical gel formulations prepared using ethylacetate extract of N. sativa have demonstrated antibacterial properties against acne-causing microorganisms, indicating its potential as an alternative remedy for dermal acne.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this can be done by inhibiting the interactions that occur between Streptococcus sanguinis and S. mutans. [7][8][9] Biofilms can be controlled by mechanical cleaning such as brushing, flossing or combined with gargling with products that contain synthetic chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies reported that black cumin has been found that the medicinal value of black cumin is because of the presence of the quinone component, phenolics, and alkaloids (Ojueromi et al, 2022). Therefore, black cumin oil is used for anticancer (Malik et al, 2021), anti-inflammatory (Noël Nyemb et al, 2022), antioxidant (Hwang et al, 2021), antibacterial (Iqbal et al, 2021), antidiabetic (Akhtar et al, 2020) and antimicrobial (Alshwyeh et al, 2022) activities.…”
Section: Introductionmentioning
confidence: 99%